2020
DOI: 10.1007/s13202-020-01020-1
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation of effect of salinity and asphaltene on IFT of brine and live oil samples

Abstract: Several factors influence the IFT of oil and formation water. These factors are rooted in the complex composition of oil, presence of different salts in water, water salinity, temperature, and pressure of reservoir. In the first part of this paper, effect of salinity on IFT between brine and an Iranian live oil sample has been studied experimentally. It is observed that IFT increases almost linearly with brine concentration. Also, linear increasing behavior of IFT with respect to pressure is obviously seen. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The oil/brine IFT was lower than the oil/deionized water IFT. This behavior is consistent with many previous studies, in which the oil/brine IFT was significantly affected by brine composition, salinity, and oil composition. The result shows that increasing the FM concentration caused a slight reduction in IFT. The 30 wt % FM solutions at different initial pH values, 6.1 and 7.0, had similar IFT values but resulted in markedly different oil recoveries (Figure ).…”
Section: Resultssupporting
confidence: 92%
“…The oil/brine IFT was lower than the oil/deionized water IFT. This behavior is consistent with many previous studies, in which the oil/brine IFT was significantly affected by brine composition, salinity, and oil composition. The result shows that increasing the FM concentration caused a slight reduction in IFT. The 30 wt % FM solutions at different initial pH values, 6.1 and 7.0, had similar IFT values but resulted in markedly different oil recoveries (Figure ).…”
Section: Resultssupporting
confidence: 92%
“…Better IFT reduction was achieved with the use of TA-2 surfactant in brines of varied salinities than TA-3 surfactant. Reduction in IFT with increase in brine salinity was observed with the use of TA-2, while increase in IFT with increase in salinity was observed with TA-3 indicating that there is a relationship between brine salinity and interfacial tension of the oleic-aqueous system, and it is dependent on the type of salt, amount of salt, type, and concentration of surfactant present [37]. This further showed the tolerance and efficiency of TA-2 surfactant in saline environments.…”
Section: Interfacial Tension Measurementsmentioning
confidence: 92%
“…Interfacial tension (IFT) is usually used as the intensity criteria of fluid–fluid interactions and as one of the dominant mechanisms for EOR in low-salinity waterflooding, as reported by Mokhtari et al., , Tetteh et al, and Farhadi et al However, due to the experimental differences, some controversial conclusions have been proposed. For ion amount, Ikeda et al, Barati-Harooni et al, and Soleymanzadeh et al reported that an increase in salinity resulted in an increase in IFT. Correspondingly, Okasha and Alshiwaish and Yousef et al observed a general trend of IFT decreases with decreasing salinity.…”
Section: Introductionmentioning
confidence: 99%